Konstribusi Ibnu Qayyim Terhadap Ayat-Ayat Hukum - Mairizal, T. (Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2018)
Ayat Aá¸¥kam can be interpreted as the verses relating to the deeds of mukallaf, either in the form of demands, preferences, or decrees. The details and classification of the verses of the law revealed by the scholars are diverse, but it shows a large number as well as evidences by the works of classical and modern scholars. Ibnu Qayyim al-Jauziyyah was known as one of the reformers in Islamic law, had a scrupulous conclusion ability, and produced over a hundred works. Nevertheless, he did not write any book related to tafsir (Intrepretation). His interpretations were spreading in his various works when he explained a matter, whether in the field of tasawwuf or fiqh. This paper analyzes the interpretations of Ibn Qoyyim from the aspects of fiqh on the issue of sale and purchase contained in his several books, but not discussed in detail as the discussion of fiqh. Furthermore, these interpretations are compared to the interpretations of other scholars to see the tendency or the postulates that he used. Ibnu Qoyyim had more comprehensive thought in understanding the verse of muamalah. Occasionally, based on the textuality of Quran and hadith, with the approach of fiqh terms to reinforce his opinion, harmony with the language aspect.